Following appendix A of "Ergoregions in Magnetised Black Hole Spacetimes" by G. W. Gibbons, A. H. Mujtaba and C. N. Pope, starting from the Lagrangian

$$\mathcal{L} = \hat{R} - \hat{F}_{\mu\nu}\hat{F}^{\mu\nu},$$ metric and field

$$\mathrm{d}\hat{s}^2 = e^{2\phi} \mathrm{d}s^2 + e^{-2\phi}(\mathrm{d}z + 2\mathcal{A})^2,\\ \hat{A} = A + \chi(\mathrm{d}z +2 \mathcal{A}),$$

after Kaluza-Klein reduction, with Killing vector $K\equiv\partial_z$ corresponding to a spatial dimension, we obtain the reduced lagrangian. After using Lagrange multipliers and dualizing the fields, we obtain $$\hat{F} = -e^{2\phi} \star \mathrm{d}\psi + d \chi \wedge (\mathrm{d}z + 2\mathcal{A}),\quad e^{-2\phi} \star F = \mathrm{d} \psi, \quad F \equiv \mathrm{d} A + 2\chi \mathrm{d}\mathcal{A},$$

where the hatted quantities are 4-dimensional, none of the fields depends on $z$ and $\star$ is the Hodge dual with respect to $\mathrm{d}s^2$. At the end, they define the complex Ernst potential by $d \Phi = i_K(\hat{\star}\hat{F} + \mathrm{i} \hat{F})$, $\Phi = \psi + \mathrm{i}\chi$, where $i_K$ is the interior product by $K$. $i_K \hat{F} = -\mathrm{d} \chi$ is easy to derive, but $\mathrm{d}\psi = i_K \hat{\star} \hat{F}$ has proved to be not so easy.

My question is about this last equation. Considering that $\det \hat{g}_{MN} = e^{4\phi} \det g_{\mu\nu}$, I obtain $$i_K \hat{\star} \hat{F} = - e^{2\phi} \star(F + 2 \mathrm{d} \chi \wedge \mathcal{A}),$$ which is obviously wrong. Could somebody provide some hint about this last equation? It must be easy to derive, but I cannot see the way at the moment.


We have $i_K\hat{\star}d \psi = \star d\psi$. Indeed, $$i_K \hat{\star} d \psi = (d \psi)^a \hat{\epsilon}_{abcd} K^b = (d\psi)_e \hat{g}^{ea} e^{2\phi} \epsilon_{acd} = (d\psi)_e g^{ea} \epsilon_{acd} = \star d \psi,$$ since $\hat{\epsilon}_{abcd} K^b = \hat{e}^0\wedge \hat{e}^1 \wedge \hat{e}^2 \wedge i_K\hat{e}^z = e^{2\phi} e^0\wedge e^1 \wedge e^2 = e^{2\phi}\epsilon_{acd}$. Also, the identity $$i_K \hat{\star} d\psi = \hat{\star} (d\psi\wedge K)$$ holds, and if we use it in the definition of $\hat{F}$, we obtain $\hat{F} = e^{2\phi}[- \hat{\star}(d \psi\wedge K) + d \chi\wedge K]$, from which the equation $i_K\hat{\star}\hat{F} = - d\psi$ follows. We observe that there is a sign error in the article. Actually, the definition of $\Phi$ is wrong, but this only becomes apparent if one attempts to relate it to the Ernst potentials.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.